Prevention of ankle sprain injuries in youth soccer and basketball: Effectiveness of a neuromuscular training program and examining risk factors - Owoeye, O. B. A.; Palacios-Derflingher, L. M.; Emery, C. A. (Clinical Journal of Sport Medicine, 2018)
Objectives: The primary objective of this study was to examine the effectiveness of a neuromuscular training (NMT) warm-up program in reducing the risk of ankle sprain injury (ASI) in youth soccer and basketball. The secondary objective included the evaluation of risk factors for ASI. Study Design: Secondary analysis of pooled data from 5 studies. Participants: Male and female youth (11-18 years) soccer and basketball players (n = 2265) in Alberta, Canada. Outcome Measures: Ankle sprain injury was the primary outcome and was recorded using a validated prospective injury surveillance system consistent in all studies. The primary exposure of interest was NMT warm-up, which included aerobic, strength, agility, and balance components. Multivariable Poisson regression, controlling for clustering by team and offset for exposure hours, was used to estimate incidence rate ratios (IRRs) with 95% confidence intervals (CIs), with considerations for confounding and effect modification and evaluating all covariates as potential risk factors. Results: A total of 188 ASIs were reported in 171 players. Neuromuscular training significantly reduced the risk of ASI [IRR = 0.68 (95% CI; 0.46-0.99)]. Independent risk factors for ASI included previous ASI [IRR = 1.98 (95% CI; 1.38-2.81)] and participation in basketball versus soccer [IRR = 1.83 (95% CI; 1.18-2.85)]. Sex, age, body mass index, and previous lower extremity injury (without previous ASI) did not predict ASI ( P > 0.05). Conclusions: Exposure to an NMT program is significantly protective for ASI in youth soccer and basketball. Risk of ASI in youth basketball is greater than soccer, and players with a history of ASI are at greater risk.